Literature Study of E-Modules Based on Project-Based Learning to Improve Critical Thinking Skills of Students - Wulandari, Ayu Mega; Handoyo, Eko; Wardani, Sri; Subali, Bambang; Widiarti, Nuni (research, training and philanthropy institution Natural Aceh, 2025)
This article aims to see how e-modules designed with the Project Based Learning (PjBL) approach can improve students' critical thinking skills. The method used is a literature review analyzing 25 relevant articles published between 2018 and 2025. This study's findings indicate that applying the Project Based Learning (PjBL) model in e-modules significantly impacts students' critical thinking skills. The project-based learning model provides opportunities for students to actively participate in solving complex problems, thus encouraging them to think critically and deeply in evaluating information. This result confirms that applying PjBL in e-modules is essential to equip students to face the challenges in the 21st century.